Neurological autoimmune diseases following vaccinations against SARS‐CoV‐2: a case series. (31st October 2021) - Kaulen, Leon D.; Doubrovinskaia, Sofia; Mooshage, Christoph; Jordan, Berit; Purrucker, Jan; Haubner, Carmen; Seliger, Corinna; Lorenz, Hanns‐Martin; Nagel, Simon; Wildemann, Brigitte; Bendszus, Martin; Wick, Wolfgang; et al.
Abstract: Background and purpose: Population‐based studies suggest that severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccines may trigger immune‐mediated thrombotic thrombocytopenia (VITT) raising concerns for other autoimmune responses. The aim was to characterize neurological autoimmunity after SARS‐CoV‐2 vaccinations. Methods: In this single‐centre prospective case study patients with neurological autoimmunity in temporal association (≤6 weeks) with SARS‐CoV‐2 vaccinations and without other triggers are reported. Clinical, laboratory and imaging data were collected with a median follow‐up of 49 days. Results: In the study period 232, 603 inhabitants from the main catchment area of our hospital (Rhein‐Neckar‐Kreis, county) received SARS‐CoV‐2 vaccinations. Twenty‐one cases (new onset n  = 17, flares n  = 4) diagnosed a median of 11 days (range 3–23) following SARS‐CoV‐2 vaccinations (BNT162b2 n  = 12, ChAdOx1 n  = 8, mRNA‐1273 n  = 1) were identified. Cases included VITT with cerebral venous sinus thrombosis ( n  = 3), central nervous system demyelinating diseases ( n  = 8), inflammatory peripheral neuropathies ( n  = 4), myositis ( n  = 3), myasthenia ( n  = 1), limbic encephalitis ( n  = 1) and giant cell arteritis ( n  = 1). Patients were predominantly female (ratio 3.2:1) and the median age at diagnosis was 50 years (range 22–86). Therapy included administration of steroids ( n  = 15), intravenous immunoglobulins in patients with Guillain–Barré syndrome or VITT ( n  = 4), plasma exchange in cases unresponsive to steroids ( n  = 3) and anticoagulation in VITT. Outcomes were favourable with partial and complete remissions achieved in 71% and 24%, respectively. Two patients received their second vaccination without further aggravation of autoimmune symptoms under low‐dose immunosuppressants. Conclusions: In this study various neurological autoimmune disorders encountered following SARS‐CoV‐2 vaccinations are characterized. Given the assumed low incidence and mostly favourable outcome of autoimmune responses, the benefits of vaccinations outweigh the comparatively small risks. Abstract : In this prospective case study, 21 consecutive cases of neurological autoimmunity, which occurred 3–23 days following SARS‐CoV‐2 vaccinations (BNT162b2 n  = 12, ChAdOx1 n  = 8, mRNA‐1273 n  = 1), are reported. Cases included vaccine‐induced immune thrombotic thrombocytopenia ( n  = 3), central nervous system demyelinating diseases ( n  = 8), inflammatory peripheral neuropathies ( n  = 4), myositis ( n  = 3), myasthenia ( n  = 1), limbic encephalitis ( n  = 1) and giant cell arteritis ( n  = 1). As outcomes were favourable in most patients and the risk of autoimmune complications appears low (<1:10, 000) the benefits of vaccination outweigh the comparatively small risks. Case numbers of several conditions were higher than expected compared to published incidences; however, population‐based studies are warranted for further investigation.